Studies of Transition States and Societies $1 (BStudies of Transition States and Societies$1 (B(STSS) aims to promote interdisciplinary exchange between scholars in all major field of thes (2010)
Studies of Transition States and Societies$1 (B(STSS) is a fast-growing open-access interdisciplinary journal for the study of transition societies. Published since 2009 it is already indexed in Scopus, the Directory of Open Access Journals (DOAJ), EBSCOs
, ProQuest, Central and Eastern European Online Library (CEEOL) and the International Political Science Abstracts (IPSA).STSS aims to promote interdisciplinary exchange between scholars in all major field of the social sciences with emphasis to so
ciology and political science. The substantive focus of the journal is on the transitional societies, particularly on the societal and political changes in the post-socialist region. Still articles on other regions are considered as well to enrich the
debate about transition in social sciences.The journal is published biannually whereas the spring issue combines articles of political science and papers in sociology are published in the fall. In addition, collections of articles about a common t
heme or debate are published as special issues.STSS is published by Institute of Political Science and Governance and Institute of International and Social Studies, Tallinn University.See more in About section.